MIMESIS AND THE PROBLEM OF SIGNIFICATION MODE: PHILOSOPHICAL AND AESTHETIC ASPECTS - Pavlova, O. (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2018)
The purpose of the work is to formulate the problem of mimesis in terms of semiotic approach and to determine its specific mode of signification. The results of the study were obtained through the application of semiotic and hermeneutic approaches, which allow the complex using of aesthetics tools as to reveal the problem of meaningful generation and the organization of signifiers in the logic of mimesis. On the basis of this scientific research, the authors developed and implemented the working curriculum of the academic discipline "Aesthetics" into educational process of Kyiv National University named after Taras Shevchenko, which is included into the Educational Curriculum "Philosophy" for bachelor degree on the specialty 6.020301 "Philosophy". Originality of this is to reveal mimesis mode of signification through the definition of the ratio of the signifier, the signified and the referent. The results obtained suggest that the development of a semiotic approach reveals the possibility of improving aesthetic component of the professional training of philosophers at Kyiv National University named after Taras Shevchenko.